SIDMA as a criterion for psychiatric compulsion: An analysis of compulsory treatment orders in Scotland. (September 2021) - Martin, Wayne; Brown, Miriam; Hartvigsson, Thomas; Lyons, Donny; MacLeod, Callum; Morgan, Graham; Schölin, Lisa; Taylor, Kathleen; Chopra, Arun
Abstract: Scottish mental health legislation includes a unique criterion for the use of compulsion in the delivery of mental health care and treatment. Under the Mental Health (Care and Treatment) (Scotland) Act, 2003, patients must exhibit 'significantly impaired decision-making ability' (SIDMA) in order to be eligible for psychiatric detention or involuntary psychiatric treatment outside the forensic context. The SIDMA requirement represents a distinctive strategy in ongoing international efforts to rethink the conditions under which psychiatric compulsion is permissible. We reconstruct the history of the Scottish SIDMA requirement, analyse its differences from so-called 'fusion law, ' and then examine how the SIDMA standard actually functions in practice. We analyse 100 reports that accompany applications for Compulsory Treatment Orders (CTOs). Based on this analysis, we provide a profile of the patient population that is found to exhibit SIDMA, identify the grounds upon which SIDMA is attributed to individual patients, and offer an assessment of the quality of the documentation of SIDMA. We demonstrate that there are systemic areas of poor practice in the reporting of SIDMA, with only 12% of CTOs satisfying the minimum standard of formal completeness endorsed by the Mental Welfare Commission. We consider what lessons might be drawn both for the ongoing review of mental health legislation in Scotland, and for law reform initiatives in other jurisdictions.